Huayñusi, planting ritual and dance of the worm killer as an Andean symbolic strategy - Motta Zamalloa, Edmundo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Huayñusi is a dance-ritual related to the planting of potatoes (Solanum tuberosum), it has a symbolic meaning that is expressed by dancing by striking the feet against the ground. It is executed in pairs and in groups. The objective of the study was to show that this dance-rite is a symbolic strategy aimed at neutralizing the threat of external biological organisms that hang over crops. The ethnographic record that comes from Andean communities of Tacna (Peru) referring to agricultural practices and rituals, leads to the conclusion that Huayñusi responds to the symbolic need to guarantee the development of the seed.